Health promotion model at the Metropolitan University of Ecuador - Cruz Xiomara Peraza de Aparicio; Florangel Josefina Benítez de Hernández; Yojanis Galeano Tamayo (Medisur, 2019)
Foundation: Among the guidelines of the Metropolitan University of Ecuador, it is essential to develop health promotion actions, which start from different groups: students, teachers, administrative and service personnel. Objective: to present a health promotion model to be applied at the Metropolitan University of Ecuador. Methods: a qualitative study was carried out based on the Health Promotion Model proposed by Nola Pender. A similar model was developed, in correspondence to the characteristics of the Metropolitan University of Ecuador. This was prepared by professors of the institution. Results: the model presented considered the joint work of the doctor, nurse, psychologist and sports coach, a team which at the same time formed the specialized support group. The strategy developed by this group was divided into four areas: two related to a stage of diagnosis or recognition of certain difficulties; and two others referred to the intervention and its result. Conclusion: the model presented constitutes a strategy to deepen the way in which individuals make decisions about their health care. The actions to be carried out by the specialized support group show the adherence to health promotion principles in this higher education center.